Individual and mixture toxicity evaluation of three pharmaceuticals to the germination and growth of Lactuca sativa seeds - Rede, Diana (2020)
This work aims to assess, individually and in mixtures, possible phytotoxic effects of three pharmaceuticals (paracetamol, ibuprofen and amoxicillin) on germination and early growth of Lactuca sativa seeds. Pharmaceuticals are an important group of emerging contaminants, whose presence has been described in several environmental compartments, including soils. However, knowledge on their possible impact in terrestrial organisms is still sparse and even more when mixtures are considered. Germination tests are important to evaluate the quality of soil and the toxic effects that contaminants can pose to plants. The acute effects of individual pharmaceuticals as well as binary and ternary mixtures were assessed using different endpoints, namely: percentage of seed germination, root elongation, shoot and leaf length, after an exposure time of five days. Overall, in the exposure of L. sativa seeds to individual pharmaceuticals there are indications of acute toxicity in the early plant growth. However, this inhibitory effect tends to be cancelled in the acute exposure to mixtures. This study shows the importance of evaluating the toxicity of mixtures of pharmaceuticals, since they might have distinct toxic effects when compared to the single compounds, and also because, probably, it is the closest scenario to the reality that can be found in the environment.